Evaluation of Nickel Neurotoxicity and High Sorption through a Hybrid Yeast / Silsesquioxane Material - Trama-Freitas, Bianca [UNESP]; Franco, Fernanda [UNESP]; Martins, Rui C.; Gando-Ferreira, Licínio M.; Quinta-Ferreira, Maria Emília; Quinta-Ferreira, Rosa Maria; do Carmo, Devaney R. [UNESP] (Springer Nature, 2020)
The presence of heavy metals in water is one of the major concerns in the public health area. So, the characterization of inorganic compounds toxicity and their detection, speciation and removal are some of the biggest environmental challenges today. Within this context, the present work evaluated the effect caused by Ni2+ in neuronal autofluorescence recorded in brain slices. Besides, a bioinorganic nanostructured hybrid material with great potential for heavy metals removal: yeast Saccharomyces cerevisiae modified with Silsesquioxane was applied for Ni2 sorption. The neurotoxicity tests revealed that in the presence of Ni2+ concentrations of 10, 20 and 30 μM (0.5, 1.0 and 1.5 ppm), irreversible autofluorescence changes occurred. In the sorption tests, the hybrid material revealed a maximum capacity of sorption of 64.6 mg/g. This material was able to reach 77.7% of removal of the initial Ni2+ solution using a 100 cm3/g liquid/solid ratio, at pH 6 and 15 min of contact time.
Keywords: Biosorption; Nickel; Silsesquioxane; Toxicity; Yeast